Desulfurization of Crumb Rubber by Modified Natural Zeolitic Catalysts - BOMBOȘ, Dorin; BOMBOȘ, Mihaela; ZAHARIA, Emilian; MÎRȚ, Andreea-Luiza; VASILIEVICI, Gabriel (Studia Universitatis Babeș-Bolyai Chemia, 2024)
The high elastomer content of the crumb rubber powder obtained from the processing of used tires increases the interest for its valorization when modifying road bitumen in order to improve its elastic characteristics. Sulfur cross-linking of elastomer chains reduces the dispersion of the crumb rubber in the road bitumen during the modification process. A novel approach was explored, involving the partial desulfurization of rubber powder using a natural zeolitic catalyst, clinoptilolite, modified in its acid form. The catalytic desulfurization of the powder was carried out in a batch system at a temperature of 280°C for six hours in the presence of high aromaticity solvents. The catalysts’ high acidity facilitated the conversion of rubber powder effectively, reaching a more suitable form to use in improving road bitumen.